Netrin-1 Therapy Restores Partial Hindlimb Movement in a Rat Model of High-Severity Chronic Spinal Cord Injury - Schmidt, Julieta (2025)
worldwide. These injuries frequently progress to a chronic phase, especially in cases of severe damage. This process results in permanent impairment, affecting both physiological functions and voluntary motor control below the lesion level. At cellular level, the formation of a glial scar, which delineates the cystic cavity, interrupts the connectivity between the central nervous system (CNS) and muscles, as well as the neural communication between the peripheral and CNSs. This process, combined with the CNS inability to promote its self-repair to prevent the progression to a chronic phase, contributes to the exacerbation of spinal cord damage, resulting in a devastating pathology. Currently, there is no effective medical treatment to address the consequences of this condition, apart from physiotherapy, which has variable success depending on the type of injury and the degree of neural tissue preservation in the affected spinal cord. Considering this last, the development of new strategies to promote neuronal repair is essential for reversing this pathology in the future. Therefore, we propose Netrin-1—a developmental guidance molecule known to direct corticospinal tract (CST) growth during CNS development— as a potential therapeutic approach for enhancing neuronal repair in severe chronic SCI. Previously, we demonstrated in an acute phase model of transected SCI that this protein effectively promotes axonal regrowth, axonal reconnection, and recovery of locomotor activity. Based on these findings, we hypothesize that Netrin-1 may additionally act as a neuroreparative molecule in chronic SCI, promoting the recovery of hindlimb movement impaired by injury. To test the therapeutic potential of this molecule, we performed a rat model of chronic SCI with a high-severity lesion at Th10–Th11 thoracic level. We demonstrate that the delivery of Netrin-1 to the epicenter of the lesion promotes significant recovery of extensive movement in the three hindlimb joints, including full flexion and extension, previously impaired by chronic injury. Additionally, it restores functional abilities such as climbing and grasping to some extent. These functional findings correlate with anatomical and cellular observations, including regrowth, sprouting and remyelination of the CST; regrowth–reconnection of extrapyramidal tracts; regrowth–reconnection of serotonergic and dopaminergic axons; prevention of transsynaptic degeneration of lower motoneurons; and neuroprotection of both myelinated sciatic nerve fibers and ascending sensory pathways. In conclusion, this study extends the neuroreparative properties of Netrin-1 to chronic conditions. These findings support its use as potential therapeutic strategy in future human clinical trials.